Effects of floor pattern on flight behaviour of the smaller tea tortrix, Adoxophyes honmai, during orientation flight in a sex pheromone plume. (8th December 2021) - Miyamoto, Ryusuke; Tabata, Jun; Kainoh, Yooichi
Abstract: Insects control their flight toward a distant odour source by integrating multimodal sensory information, such as olfactory and visual information. Control of flight speed in orientation flight toward an odour source using visual patterning below has been observed in many species of moths. However, there are few reports about moth flight behaviour over solid‐coloured floors. To examine, which visual stimuli affect flight behaviour of moths, male smaller tea tortrix ( Adoxophyes honmai ) were released in a pheromone plume over two striped floors (longitudinal and transverse stripes) and two unpatterned floors (solid white and solid black). Flight behaviours were videotaped, and upwind flight speed, height (altitude) and the number of backward movements moths made as they approached the pheromone source were determined. Male moths significantly increased mean and maximum upwind flight speed over longitudinal stripes relative to their speed over transverse stripes. Their speed over a solid black floor was the fastest of all floor patterns tested. As males approached the pheromone source, their mean upwind speed decreased significantly over all floor patterns, except for the black floor. Fewer moths made backward movements over the black floor compared with the other three floors. In addition, male moths flew significantly higher over the white floor than over the other three floors, while 60–40 cm from the pheromone source. This is the first time that differences in moth flight behaviour over two patternless floors have been reported. These results suggest that orientation flight behaviour of male moths is affected not only by visual patterns, but also by the reflectance or reflected wavelength spectrum of the floor. Abstract : Male Adoxophyes honmai increased mean and maximum upwind flight speed over a solid black floor relative to their speeds over floors with transverse and longitudinal stripes, and over a solid white floor, in a sex pheromone plume. As male A. honmai approached the pheromone source, their mean upwind speed tended to decrease over all floor patterns tested, although the decrease was not significant over the solid black floor. Male A. honmai flew higher over the white floor than over the other floor patterns tested, including the solid black floor in the centre segments of the wind tunnel.